Le rose in fila Rose selvatiche e coltivate: una storia che parte da lontano - Bessi, Franca Vittoria (Studi e saggi, 2018)
The volume traces the fundamental stages of the transition from wild roses to cultivated roses, taking as a starting point the systematics of the genus Rosa and linking it to a thousand stories concerning plant hunters, breeders, geographic explorations, the work of scholars and gardeners, enthusiasts, collectors. This book also offers some information on the use of the rose in gardening, cooking and medicine, as well as a large iconography created mostly in the Florence Botanical Garden, a glossary of technical terms and identification elements for horticultural roses.